A GRADUATE CURRICULUM IN ACCOUNTING. - Dohr, Jmes L. (The Accounting Review, 1948)
Abstract The article presents a brief description of a graduate curriculum in accounting. It begins at the introductory level and extends over a period of two years. It includes the very interesting and important problem of providing accounting instruction for nontechnical students. As liberal arts graduates the students will have had a minimum of two years' additional instruction at the university level and, as liberal arts go these days, they will have had something in the way of a background in such areas as economics, banking, statistics, etc. The program of the first semester is designed to lay a foundation. The student is to be acquainted with economic resources and activities. In the second semester the student continues his study of accounting and law while he explores the administrative problems in the three basic fields of production, distribution, and finance. The second year is wholly one of accounting study in the basic areas of principles, costs, verification, taxation and research.